2014
DOI: 10.3748/wjg.v20.i37.13343
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy in pancreatic cancer

Abstract: Pancreatic cancer (PC) is a highly lethal disease and notoriously difficult to treat. Only a small proportion of PC patients are eligible for surgical resection, whilst conventional chemoradiotherapy only has a modest effect with substantial toxicity. Gene therapy has become a new widely investigated therapeutic approach for PC. This article reviews the basic rationale, gene delivery methods, therapeutic targets and developments of laboratory research and clinical trials in gene therapy of PC by searching the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 184 publications
0
56
0
Order By: Relevance
“…12,13 Inhibition of cell viability and proliferation activity could be attributable to the induction of cell apoptosis in PC cells. 12,13 Therefore, whether the cell growth suppression observed was induced by apoptosis was then examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Inhibition of cell viability and proliferation activity could be attributable to the induction of cell apoptosis in PC cells. 12,13 Therefore, whether the cell growth suppression observed was induced by apoptosis was then examined.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Inhibition of cell viability and proliferation activity could be attributable to the induction of cell apoptosis in PC cells. 12,13 Therefore, whether the cell growth suppression observed was induced by apoptosis was then examined. In this study, treatment of PANC-1 and BxPC-3 cells with sporamin showed DNA fragmentation or nuclear condensation in the nucleus measured using DAPI staining, which is typically observed in apoptotic cells, and a significant increase in the percentage of apoptotic cells was confirmed by flow cytometer.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately clinical results did not reflect those positively obtained in vitro [19,38,67,68,69,70]. A compound is now evaluated at the clinical stage, the LODER ® (Silenseed Ltd., Modi’in, Israel) that is a miniature biodegradable intratumoral implant containing and releasing within 4 months siRNA against Kras .…”
Section: Therapeutic Genes and Pre-clinical Strategiesmentioning
confidence: 99%
“…According to recent literatures, ErbB signaling pathway and TGF-beta signaling pathway participate in the transmembrane signal transduction of pancreatic cancer [13, 14]. Such transmembrane signal transduction pathways have been further validated to transfer the signals to intracellular pathways (such as p53 signaling pathway, MAPK signaling pathway, PI3K-Akt signaling pathway, and VEGF signaling pathway) [13, 1517]. Intracellular signaling pathways have been identified to contribute to the abnormal proliferation of pancreatic cells and further initiate the tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%